The Dark Side of Political Marketing: Islamist Propaganda, Reversal Theory and British Muslims - Baines, Paul R.; O'Shaughnessy, Nicholas J.; Moloney, Kevin; Richards, Barry; Butler, Sara; Gill, Mark (Emerald Group Publishing Limited, 2010)
Purpose This article discusses exploratory research into the perceptions of British Muslims towards Islamist ideological messaging to contribute to the general debate on ‘radicalisation'. The article discusses the findings of discussion groups in the light of research previously undertaken in the propaganda/psychology fields, from the perspective of Reversal Theory. Methodology/approach Four focus groups were undertaken with a mixture of Bangladeshi and Pakistani British Muslims who were shown a selection of Islamist propaganda media clips, garnered from the internet. The research is intended to provide exploratory indications of how British Muslims receive Islamist communication messages in order to provoke further research in this critical field. Findings We propose that Islamist communications focus on eliciting change in emotional states, specifically inducing the paratelic-excitement mode, by focusing around a meta-narrative of Muslims as a unitary grouping self- defined as victim to Western aggression. Early indicators are that some genres of Islamist propaganda may be more effective than others in generating these emotional change states (e.g. cartoons) and some groupings appear to be more susceptible than others. We conclude that our British Muslim respondents were unsympathetic to the Islamist ideological messaging contained in our sample of propaganda clips. Research limitations/implications The research highlights the difficulties in undertaking research in such a sensitive field. We propose a series of four testable propositions to guide future research looking specifically at whether those subjects who are more likely to be excited by Islamist communication include those with weakly held identities, younger males, those feeling contempt for Western culture, and the use of specific media genre formats. Originality/value of paper The article provides an insight into how British Muslims might respond to Islamist communications, indicating that whilst most are not susceptible to inducement of paratelic-excitement, others are likely to be, dependent on which genre of clip is used, the messages contained therein, and who that clip is targeted a